Trends in European minimum wage schemes: foundations for a European policy - Sánchez-Vellvé, Francisco J. (2021)
This paper studies the characteristics of the minimum wage regimes of the EU Member States and what are the registered trends in recent years. Based on the fundamental dimensions of minimum wage systems, we develop a multiple correspondence analysis (MCA) that allows us to know the relative positioning of Member States with respect to them, confirm the existing differences among systems, as well as to glimpse the more shared characteristics on which a European minimum wage scheme could be established. To complete the analysis, we reflect on an explanatory framework of the driving forces that lead the way in which statutory minimum wage is materialized in each Member State, and thus understand some of the difficulties that exist for the consolidation of a single minimum wage scheme for the European Union.